2009
DOI: 10.1038/cr.2009.30
|View full text |Cite
|
Sign up to set email alerts
|

PSD-95 regulates D1 dopamine receptor resensitization, but not receptor-mediated Gs-protein activation

Abstract: The present study aims to define the role of postsynaptic density (PSD)-95 in the regulation of dopamine (DA) receptor function. We found that PSD-95 physically associates with either D1 or D2 DA receptors in co-transfected HEK-293 cells. Stimulation of DA receptors altered the association between D1 receptor and PSD-95 in a time-dependent manner. Functional assays indicated that PSD-95 co-expression did not affect D1 receptor-stimulated cAMP production, Gs-protein activation or receptor desensitization. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Indeed, PSD-95 uncouples NMDA receptor-dependent enhancement of D1 signaling through the inhibition of D1-NMDA receptor association and has been demonstrated to physically interact with D2 receptors in cell cultures [130,176]. A growing number of postmortem human brain as well as preclinical studies have suggested an implication of PSD-95 in the pathophysiology of schizophrenia [177][178][179][180].…”
Section: Focus On Psd Scaffolding Proteins In Dopamine-glutamate Intementioning
confidence: 97%
“…Indeed, PSD-95 uncouples NMDA receptor-dependent enhancement of D1 signaling through the inhibition of D1-NMDA receptor association and has been demonstrated to physically interact with D2 receptors in cell cultures [130,176]. A growing number of postmortem human brain as well as preclinical studies have suggested an implication of PSD-95 in the pathophysiology of schizophrenia [177][178][179][180].…”
Section: Focus On Psd Scaffolding Proteins In Dopamine-glutamate Intementioning
confidence: 97%
“…HEK293 membrane P2 fractions were prepared using the method described previously (Sun et al, 2009). In brief, cells were collected and lysed in hypotonic buffer [5 mM Tris-HCl and 2 mM EDTA (pH 7.4)] containing a protease inhibitor mixture (Sigma-Aldrich) and were sonicated three times for 18 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…PSD-95 has also been reported to positively regulate dopamine 1 receptor (D 1 R) endocytosis and inhibit D 1 R-mediated cAMP formation (Zhang et al, 2007b). A more recent study suggests that PSD-95 contributes to D 1 R recycling and resensitization without influencing D 1 R-mediated Ga s activation (Sun et al, 2009). However, the methods and cellular contexts used to arrive at these conclusions in these various studies are not directly comparable.…”
Section: Gpcr-interacting Psd-95 Family Pdz Domain-mentioning
confidence: 99%